1981
DOI: 10.1021/ja00393a004
|View full text |Cite
|
Sign up to set email alerts
|

Protein hydration from water oxygen-17 magnetic relaxation

Abstract: Water oxygen-17 magnetic relaxation is shown to be a powerful technique for studying protein hydration. Longitudinal and transverse I70 relaxation rates were measured at variable frequency (4-35 MHz), temperature, pH, and protein concentration in aqueous solutions of seven proteins. The data were analyzed in terms of a fast exchange two-state model with local anisotropy.A water l70 quadrupole coupling constant of 6.67 MHz and an order parameter of 0.06 (from 170 splittings in lyotropic liquid crystals) results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
135
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(140 citation statements)
references
References 1 publication
5
135
0
Order By: Relevance
“…Rather, we focus on the more readily interpreted 17 O relaxation data reported earlier (Halle et al, 1981;. While essentially the same conclusions as here were reached about the fast rotation of surface water molecules, it was also shown that the low-frequency relaxation contribution (b term) could be consistently accounted for in terms of the same (weakly ordered) surface water molecules whose fast (but orientationally restricted) rotation is responsible for the high-frequency contribution (a term).…”
Section: Concluding Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Rather, we focus on the more readily interpreted 17 O relaxation data reported earlier (Halle et al, 1981;. While essentially the same conclusions as here were reached about the fast rotation of surface water molecules, it was also shown that the low-frequency relaxation contribution (b term) could be consistently accounted for in terms of the same (weakly ordered) surface water molecules whose fast (but orientationally restricted) rotation is responsible for the high-frequency contribution (a term).…”
Section: Concluding Discussionsupporting
confidence: 71%
“…In connection with previous 17 O relaxation studies, two weighty arguments were advanced in favor of a relaxation dispersion induced by a weakly ordered hydration layer (Halle et al, 1981;. First, the normalized relaxation dispersion step did not vary much among the half-dozen proteins examined, contrary to what would be expected if the dispersion was due to a small number of highly ordered water molecules in specific binding sites.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…NMR studies of protein hydration in aqueous solution give a range of residence times, 10 Ϫ2 -10 Ϫ8 , for interior water and subnanosecond for surface water, as shown by the groups of Wüthrich (12) and Forsén (33) and others. Because of the femtosecond resolution achieved here, we decided to reexamine the same protein, but when denatured.…”
Section: Resultsmentioning
confidence: 78%
“…In fact, the percentage of apolar amino acid residues that are associated with protein hydrophobicity are about 50 and 37% for BSA and IgG, respectively, suggesting that BSA-covered beads are more hydrophobic. 46 Figure 6.10 reveals that the spherical geometry of Pluronic-adsorbed beads is much less defined, relative to bare beads. They appear much larger in diameter and have a wider size distribution.…”
Section: Afm Analysismentioning
confidence: 99%